0462 Baseline Sleep Disturbance and Inability to Discontinue Chronic Hypnotic Use. (25th May 2022) - Koshorek, Gail; Parashar, Vartika; Roth, Thomas; Roehrs, Timothy
Abstract: Introduction: Clinicians prescribing hypnotics remain concerned regarding the inability to discontinue hypnotics after chronic use, which has never been directly tested in a controlled prospective study using self-administration choice methodology. This study reports on difficulty discontinuing medication as a function of basal sleep disturbance in insomnia subjects instructed to stop taking their study medication after 6 months of nightly use. Methods: DSM-V diagnosed insomnia subjects, aged 23-61 yrs, (n=39, 34 females), with no other sleep disorders, unstable medical or psychiatric diseases or drug dependency completed the trial. Following a screening polysomnogram participants were randomized to zolpidem XR (12.5 mg), eszopiclone (3 mg), or placebo nightly for 6 months (blinded groups A: n=15, B: n=11, C: n=13). After 6 months, nightly use, over a 2-week choice period, they were instructed to discontinue hypnotic use, but if necessary, to self-administer either 1, 2, or 3 capsules of their assigned "blinded" medication (zolpidem XR 6.25 mg, 6.25 mg, placebo; eszopiclone 2 mg, 1 mg, placebo as capsules 1, 2 and 3 respectively; or 3 placebos). Results: Over the 14 nights 20 subjects took zero (51%) capsules; among the 19 taking capsules the median number chosen was 3. Most took one capsule per night; 6 took > 1 capsules on a given night. Importantly 1 subject took every capsule (42) available. Overall, the number of capsules taken declined from week 1 to 2 (p< .005). Those with baseline PSG SE <81% did not reduce capsule choice from week 1 to 2 (p<.02). Group A choose more capsules than groups B and C (p<.01). Conclusion: The majority (85%) of the participants discontinued 6-month nightly hypnotic use (i.e. took < 6 total capsules over the 14 discontinuation nights) and among those taking capsules the rate declined from week 1 to 2. Baseline SE <81% may help identify those with difficulty discontinuing. Support (If Any): NIDA, grant#: R01DA038177 awarded to Dr. Roehrs.